Determinants of Mergers and Acquisitions in Emerging Asian Countries: Effects of Confucianism and Technological Development - Nikita Larchenko; Liudmila Ruzhanskaya (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
Asian emerging markets exemplify the contemporary trend of glocalization (globalization-localization). Countries in this region have strong cultural bonds shaped by the influence of Confucianism, which has given rise to a distinctive approach to conducting business, including the realm of mergers and acquisitions. The homogeneity of cultural values fosters trust among parties even in cross-border transactions, impacting the assessment of transaction premiums. Simultaneously, within this region, a cluster of Asian Tiger countries distinguishes itself by leading in technological advancements, particularly in the realm of digitalization. The escalating competitiveness of technologically advanced companies further influences estimates of transaction premiums.This paper endeavors to delve into the theoretical aspects of these issues and substantiate, through empirical evidence, the cultural impact of Confucianism and technological progress on mergers and acquisitions (M&A). Our research is grounded in a database encompassing 2677 cross-border deals compiled from January 1, 2002, to January 1, 2021, for 10 burgeoning Asian markets. This study marks the first exploration of M&A deal value and firm valuation during transactions utilizing a glocal region as a case study. Our primary findings substantiate the notion that cultural affinities exert a substantialinfluence on M&A deal values, with a propensity for lower values among culturally similar countries. Congruent cultural values build trust among stakeholders and safeguard from additional risks. These results give policymakers and business entities an opportunity to adjust their decisions and refine their comprehension of factors that shape the economy.